Conceptualizing community resilience: Revisiting conceptual distinctions. Issue 1 (1st January 2017) - Matarrita-Cascante, David; Trejos, Bernardo; Qin, Hua; Joo, Dongoh; Debner, Sigrid
Abstract: Community development and related approaches have become prominent in academic circles, resulting in the emergence and resurgence of related community-level notions. With the expansion of terms, conceptual confusions have surfaced. The notion of community resilience has gone through this process, as its development/understanding is still in progress. Community resilience has been misused/confused with other notions including community agency, community vulnerability, community adaptability, and community capacity. Our goal here is to provide conceptual clarification to the term community resilience by reviewing and contrasting it with the above-mentioned notions. We argue that while similitudes exist within these concepts, they are bounded by their literatures fed by different fields of study, resulting in different goals (i.e. problem solving, response to change, and risk mitigation) in varying contexts. Despite their differences, we offer explanations of how the concepts are interrelated, in addition to noting the differences in the levels of conceptualization that each literature offers. We concluded that community resilience provides a better framework for understanding community change and how it is addressed.